Heroes and victims - Masaryk, Jan (London : Czechoslovak Ministry of Foreign Affairs Infomation Service Lincolns-Prager, 1945)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; oorlogsslachtoffers; Tsjecho-Slowakije.